Korean religions in relation : Buddhism, Confucianism, Christianity - Min, Anselm K., 1940-2020; Kang, Wi Jo, 1930- (SUNY series in Korean studies., 2016)
Examines Buddhism, Confucianism, and Christianity in Korea, focusing on their mutual accommodation, exclusion, conflict, and assimilation. Instead of simply being another survey of the three dominant religions in contemporary Korea--Buddhism, Confucianism, and Christianity--this unique book studies them in relation to each other in terms of assimilation, accommodation, conflict, and exclusion. The contributors focus on major issues that have historically challenged the relations between the three religions from the Goryeo period to the present and how each religion has responded to them. The essays bring a new perspective to the study of Korean religions, one that is especially pertinent in the current age of religious pluralism with all its tensions. Anselm K. Min is Professor of Religion at Claremont Graduate University and the author and editor of many books, including Dialectic of Salvation: Issues in Theology of Liberation, also published by SUNY Press.